(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of medication adherence and identify associated factors among psychiatric outpatients treated at Ca Mau General Hospital in 2025. Methods: A cross-sectional descriptive study was conducted on 142 psychiatric outpatients. Medication adherence was assessed using the 8-item Morisky medication adherence scale. Logistic regression analysis was employed to identify factors associated with adherence levels. Results: The rate of medication adherence was 47.18%, while 52.82% of patients were non-adherent. Multivariate logistic regression analysis indicated that factors significantly associated with adherence included: age group ≤ 40 years (aOR = 5.12), education level of high school or higher (aOR = 1.78), living with relatives (aOR = 3.45), family supervision and management of medication (aOR = 2.51), daily family support for medication intake (aOR = 2.14), and a distance from home to the pharmacy ≤ 10 km (aOR = 2.02), all with p < 0.05. Conclusions: The rate of medication adherence among psychiatric outpatients remains low. Associated factors primarily relate to individual characteristics, family support, and accessibility to healthcare services. Interventions to enhance adherence are necessary, particularly for older patients and those lacking family support.